2014
DOI: 10.1111/and.12370
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of lemon balm (Melissa officinalis) and mate tea(Ilex paraguensys)on quality, lipid peroxidation and DNA oxidation of cryopreserved boar epididymal spermatozoa

Abstract: In this study, we investigated the protective ability of the addition of two antioxidant herb extracts, mate tea and lemon balm, on boar epididymal frozen-thawed spermatozoa quality. Testes from mature boars were collected at local slaughterhouse, and sperm samples from epididymis were recovered by flushing. Spermatozoa were cryopreserved in lactose-egg yolk buffer supplemented with various concentrations of lemon balm and mate tea (0, 2.5, 5 and 10 g l(-1) ) using the straw-freezing procedure. Motion paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
(49 reference statements)
2
13
0
1
Order By: Relevance
“…The thyroid gland plays a critical role in the synthesis of fatty acids and the degradation of lipids Wang et al (2008); therefore, thyroid dysfunction is often associated with weight gain and elevated glucose levels Pucci et al (2000) and Luño et al (2015). Our results coordinate with that results which indicate an increase in body weight and minimal increasing in glucose levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The thyroid gland plays a critical role in the synthesis of fatty acids and the degradation of lipids Wang et al (2008); therefore, thyroid dysfunction is often associated with weight gain and elevated glucose levels Pucci et al (2000) and Luño et al (2015). Our results coordinate with that results which indicate an increase in body weight and minimal increasing in glucose levels.…”
Section: Discussionsupporting
confidence: 90%
“…Its leaves are used in Iranian folk medicine for management of many disorders as it has high capacity of antioxidant properties through its chemical compounds including high amount of flavonoids, rosmaric acid, gallic acid and phenolic contents Miraj et al (2017). Many studies demonstrated that the cytoprotective effect of lemon balm extracts seen in rats was partly due to free radical scavenging properties Luño et al (2015). Moreover, it could protect against oxidative damage induced by various pro-oxidant agents that induce lipid peroxidation by different processes.…”
Section: Discussionmentioning
confidence: 99%
“…Melissa officinalis has been reported to demonstrate high levels of antioxidant properties through its chemical constituents including high amount of phenolic compound, flavonoids and gallic and rosmaric acid (Miraj et al., ). In an animal study on cryopreserved spermatozoa of boars, the protective ability of extracts of lemon balm was investigated; it was indicated that administration of lemon balm improves amplitude of lateral head displacement after thawing, curvilinear trajectory and straightness of spermatozoa (Luno et al., ). Martins et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus these findings indicate that arteries and skin are good targets for in vivo studies of LBE. LB is reported to provide beneficial effects on cognitive function in clinical trials (18), psychological stress in an animal model (19), and suppression of oxidation in an in vitro study (33). However, there have been few studies of the effect of LB on arteries and skin.…”
Section: Discussionmentioning
confidence: 99%